PEMBINAAN PENYUSUNAN LAPORAN KEUANGAN DENGAN PENGGUNAAN SAK EMKM PADA PELAKU UMKM DI KAVLING FLAMBOYAN - Viola Syukrina E Janrosl; Kiki Futich Rosida; Annisa Anugrah Maulidina (Bakti Cendana, 2019)
Financial management is one of the important aspects for the progress of the company. Financial management can be educated through accounting. Accounting is a systematic process to produce financial information that can be used for decision making for its users. Can help the development of MSMEs Mainly in financial matters. Phenomenon in carrying out business activities MSME managers feel difficulty in recording what happened in the operations of their business. The difficulty is the result of and results achieved by each business. Used to conduct and measure activities that occur in business activities and non-business activities. This phenomenon attracted the interest of the service proponent team to hold service activities carried out to provide guidance to 3 MSMEs in the Flamboyan Plot. There are krispy banana businessmen, grilled meatballs and onion cakes. Community Service is carried out so that it can be a structured bookkeeping in financial statements that is well in accordance with EMKM standards and able to provide financial services, for which neglect provides a way to make financial reports based on the EMKM GAAP. Add insight to the coaching participants, namely the krispy banana businessmen, grilled meatballs and cakes in the Flamboyan Plot.